2004
DOI: 10.1074/jbc.m401232200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 2H NMR at Natural Abundance Can Distinguish the Pathway Used for Glucose Fermentation by Lactic Acid Bacteria

Abstract: For any given metabolic pathway, isotope redistribution coefficients (a ij ) that characterize the specific derivation of each hydrogen atom can be defined. By using quantitative deuterium NMR, the redistribution of deuterium at natural abundance in lactic acid produced by the bacterial fermentation of glucose has been determined for each non-labile hydrogen atom of glucose or water and the hydrogen atoms of lactic acid. Distinct differences are observed in the lactic acid isolated from Lactococcus lactis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…The data used to obtain Equations 9 -15 are quantitative and obtained under uniform conditions. Therefore, the conversion factor (C f ), which represents quantitatively the extent to which each 2 H of glucose is retained in the ethanol produced, can be calculated (2,5). This factor is dependent on the stoichiometry of the overall bioconversion (Reaction 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data used to obtain Equations 9 -15 are quantitative and obtained under uniform conditions. Therefore, the conversion factor (C f ), which represents quantitatively the extent to which each 2 H of glucose is retained in the ethanol produced, can be calculated (2,5). This factor is dependent on the stoichiometry of the overall bioconversion (Reaction 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five spectra were recorded for each sample and an exponential multiplication associated with a line broadening of 0.5 Hz was used. The quantitative measurement of the areas under the peaks and the calculation of the ( 2 H/ 1 H) i ratios were carried out as described previously (5 …”
Section: Ppm)mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we have shown by isotopic quantitative 2 H NMR spectrometry that the isotopic fractionation in 2 H is distinctive depending on whether the Embden-Meyerhof-Parnas (EMP) 3 pathway or the reductive pentose phosphate (RPP) pathway is used and that the hydrogen atoms in the product can be linked to the positions in the substrate (1,2).…”
mentioning
confidence: 99%
“…Likewise, it can provide evidence to distinguish between different pathways to obtain the same product (9,10).…”
Section: Significancementioning
confidence: 99%